2019
DOI: 10.1101/654616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of 3’ UTR motifs required for mRNA localization to myelin sheaths in vivo

Abstract: Myelin, a specialized membrane produced by oligodendrocytes, insulates and supports axons.Oligodendrocytes extend numerous cellular processes to wrap multiple axons, and myelin sheaths differ in length and thickness. Notably, neuronal activity can modify sheath characteristics. How myelin formation is controlled at sites distant from oligodendrocyte cell bodies is not well known. Using zebrafish, we tested the possibility that 3' untranslated regions (UTRs) influence localization of myelin mRNAs, thereby enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…The localization of mRNAs (Ainger et al, 1993;Thakurela et al, 2016;Yergert et al, 2021), ribosomes (Lunn et al, 1997), and RNA binding proteins (Doll et al, 2020) in distal myelin sheaths support a model where local protein translation promotes myelination. We therefore investigated the possibility that translation factors that are regulated by mTOR signaling are localized to nascent myelin sheaths.…”
Section: Oligodendrocytes Localize Mtor-regulated Translational Machi...mentioning
confidence: 71%
See 1 more Smart Citation
“…The localization of mRNAs (Ainger et al, 1993;Thakurela et al, 2016;Yergert et al, 2021), ribosomes (Lunn et al, 1997), and RNA binding proteins (Doll et al, 2020) in distal myelin sheaths support a model where local protein translation promotes myelination. We therefore investigated the possibility that translation factors that are regulated by mTOR signaling are localized to nascent myelin sheaths.…”
Section: Oligodendrocytes Localize Mtor-regulated Translational Machi...mentioning
confidence: 71%
“…In support of this possibility, free ribosomes have been observed by electron microscopy in the distal ends of cultured oligodendrocytes (Lunn et al, 1997) and recently hundreds of other myelin resident mRNAs have been identified (Thakurela et al, 2016) and a subset validated in vivo (Yergert et al, 2021).…”
Section: Introductionmentioning
confidence: 89%
“…Embryos were raised at 28.5°C in embryo medium and staged as hours or days post fertilization (hpf/dpf) according to morphological criteria [53]. Zebrafish lines used in this study included fmr1 hu2787 [34], Tg(sox10:mRFP) vu234 [32], Tg(sox10:tagRFP) co26 [38], Tg(mbp:EGFP-CAAX) co58 [54], and Tg(olig2:EGFP) vu12 [55]. All other constructs were delivered by transient transgenesis to facilitate sparse labeling and single cell analysis.…”
Section: Zebrafish Lines and Husbandrymentioning
confidence: 99%
“…Oligodendrocytes of the central nervous system (CNS) and Schwann cells in the peripheral nervous system (PNS) generate the myelin sheath, covering axons to a proper propagation of neural signal at a high speed with a diminution of ionic leakiness, as well as preserving structures from degeneration [ 1 3 ]. In fish, myelination is conserved across species at a molecular and cellular level and also showed high conserved mechanisms with mammals [ 4 ].…”
Section: Introductionmentioning
confidence: 99%